Always an outlaw: Daughters-in-law on Australian family farms - Pini, Barbara (Elsevier Ltd, 2007)
This article explores the position of women as daughters-in-law on family farms in Australia. The significance of this focus relates to the fact that family farming continues to be the main form of agricultural operation in most western countries. Women typically come to farming through marriage, meaning that most experience being a 'daughter-in-law' on a family farm. Drawing on notions of subjectivity, discourse and agency, the article explores the meanings and experiences connected with the identity of 'daughter-in-law' on family farms. The article concludes by speculating on how shifts in gender and agricultural discourses may destabilize the traditional identity of 'daughter-in-law' within family farming as well as by considering the implications of such a destabilization.